Heparin-induced thrombocytopenia - Warkentin, Theodore E., 1960-; Greinacher, Andreas (Boca Raton, Florida ; London ; New York : CRC Press, 2013)
Suitable for clinicians and hematology consultants, this title includes: coverage of approved and novel pharmacotherapies, dosing guidelines, and the advantages and limitations of alternative anticoagulants; review of the immune basis and pathogenesis, animal models, and laboratory testing for HIT antibodies; and more.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Heparin -- Side effects; Electronic books